2008
DOI: 10.1016/j.cbpa.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythms of body temperature and heat production of sibling mastomys species from different ecosystems — The response to photoperiod manipulations

Abstract: We compared body temperature (T b ) and metabolic rates, measured as oxygen consumption (VO 2 ), daily rhythms of two sibling species of the genus Mastomys. We also studied their responses to long day (16L: 8D, LD) and short day (8L: 16D, SD) photoperiod manipulations at a constant ambient temperature of 26 + 1°C. We noted significant differences in T b and VO 2 daily rhythm patterns, under SD and LD-acclimation between the sibling species. These differences explain adaptation to the climatic conditions that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
1
8
0
1
Order By: Relevance
“…In fact, the magnitude of the difference in intrinsic MR between species adapted to different environments ranges between 9 and 20%. For example, the difference was 8-16% in mice (Haim et al, 2008) and 9-20% in polychaetes (Gamenick et al, 1998;Linke-Gamenick et al, 2000). Even for species with intrinsically different MRs, additional factors are probably necessary to account for their ability to exist in extremely divergent environments.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, the magnitude of the difference in intrinsic MR between species adapted to different environments ranges between 9 and 20%. For example, the difference was 8-16% in mice (Haim et al, 2008) and 9-20% in polychaetes (Gamenick et al, 1998;Linke-Gamenick et al, 2000). Even for species with intrinsically different MRs, additional factors are probably necessary to account for their ability to exist in extremely divergent environments.…”
Section: Discussionmentioning
confidence: 94%
“…Tieleman et al measured MR across several related genera of birds and found a strong relationship between native aridity and metabolic rate (Tieleman et al, 2003). In contrast, when Haim et al measured MR across a range of photoperiods and times of the day of two sibling species of mice, one of which was arid adapted, there was not a significant difference in MR for most intervals tested (Haim et al, 2008). The authors concluded that a difference in MR was not responsible for the adaptation.…”
Section: Introductionmentioning
confidence: 85%
“…Light:dark cycles are a common Zeitgeber for the entrainment of the mammalian biological clock and the main cue for their seasonal acclimatization (Aschoff et al, 1982;Haim et al, 2008). Disruption of scotophase by light results in physiological and hormonal changes that activate stress (Bass and Takahashi, 2010;Zubidat et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductance was computed at thermoneutrality, as C = RMR/(T b − T a ), where T b is body temperature after RMR estimation (Seymour et al 1998). Additionally, other parameters were obtained, as metabolic water production (MWP = RMR * 0.62 mg H 2 O/ml O 2 -Schmidt-Nielsen and Schmidt-Nielsen 1950b; MacMillen and Hinds 1983), evaporative heat loss (EHL = TEWL * 0.603 cal/mg H 2 O; see Stitt 1976;Huynh et al 2007), and heat production (HP = RMR * 5.011 cal/ml O 2 ; see Haim et al 2008).…”
Section: Methodsmentioning
confidence: 99%